Brain regulation of feeding behavior and food intake in fish - Lin, Xinwei; Volkoff, Hélène; Narnaware, Yuwaraj; Bernier, Nicholas J.; Peyon, Pierre P.; Peter, Richard E. (My University, 2000)
In mammals, the orexigenic and anorexigenic neuronal systems are morphologically and functionally connected, forming an interconnected network in the hypothalamus to govern food intake and body weight. However, there are relatively few studies on the brain control of feeding behavior in fish. Recent studies using mammalian neuropeptides or fish homologs of mammalian neuropeptides indicate that brain orexigenic signal molecules include neuropeptide Y, orexins, galanin and β-endorphin, whereas brain anorexigenic signal molecules include cholecystokinin, bombesin, corticotropin-releasing factor, cocaine- and amphetamine-regulated transcript, and serotonin. Tachykinins may also have an anorectic action in fish. The brain hypothalamic area is associated with regulation of food intake, while sites outside the hypothalamus are also involved in this function. There is correlation between short-term changes in serum growth hormone levels and feeding behavior, although possible mechanisms integrating these functions remain to be defined.
Keywords: feeding; neuropeptide; growth hormone; brain; fish